The Relationship Between Childhood Trauma and Histrionic Personality Among University Students (Journal of the College of Basic Education, 2026)
The current research aims to identify childhood trauma among university students, and the difference in it according to the gender variable (males - females), and the histrionic personality, and the difference in it according to the gender variable (males - females), and the correlation between childhood trauma and histrionic personality. To achieve the research objectives, a scale for childhood trauma and another for histrionic personality were adopted. They were translated into Arabic, and then their psychometric properties of validity and reliability were calculated after applying them to a sample of university students (375) males and females. The results indicated that university students did not suffer from any type of childhood trauma, and there was no difference between males and females in each of emotional neglect, physical neglect, and physical abuse, but there was a difference between them in favor of females in emotional abuse and sexual abuse. The results showed that the research sample did not have a histrionic personality. However, males were more hysterical than females, and were more seductive (a domain of the histrionic Personality) than females. There was a positive relationship between physical neglect, emotional abuse, physical abuse, sexual abuse, and the hysterical personality. Based on these findings, the research came up with a set of recommendations and proposals.